Essential quality practices in Indonesian manufacturing SMEs - Mohd. Nizam, Ab. Rahman, Dr.; Hernadewita; Baba, Md. Deros, Assoc. Prof. Dr.; Ahmad Rasdan, Ismail (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/